FibroAtlas: A Database for the Exploration of Fibrotic Diseases and Their Genes. (30th December 2019) - Liu, Jinying; Sun, Dezhi; Liu, Jiale; Xu, Hao; Liu, Yuan; Li, Yang; Diao, Lihong; Wang, Xun; Wang, Dan; Tian, Lei; Zhang, Huimin; Liu, Zhongyang; et al.
Abstract : Background . Fibrosis is a highly dynamic process caused by prolonged injury, deregulation of the normal processes of wound healing, and extensive deposition of extracellular matrix (ECM) proteins. During fibrosis process, multiple genes interact with environmental factors. Over recent decades, tons of fibrosis-related genes have been identified to shed light on the particular clinical manifestations of this complex process. However, the genetics information about fibrosis is dispersed in lots of extensive literature. Methods . We extracted data from literature abstracts in PubMed by text mining, and manually curated the literature and identified the evidence sentences. Results . We presented FibroAtlas, which included 1, 439 well-annotated fibrosis-associated genes. FibroAtlas 1.0 is the first attempt to build a nonredundant and comprehensive catalog of fibrosis-related genes with supporting evidence derived from curated published literature and allows us to have an overview of human fibrosis-related genes.